Urgensi, Fungsi, dan Pendekatan Filsafat Pendidikan Islam - Safitri, Evi; Shaqinah, Nanda; Nafi’ah, Romdhiatin (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Philosophy of islamic education is a branch of science that examines the foundations of education in islam. Understanding the urgency, Function and philosophical approach of islamic education is important in realizing quality education based on islamic values. This research aims to understand the urgency of islamic educational philosophy in the context of modern education, examine the function of islamic education in directing educational goal and pratices, analyze various approaches to islamic educational philosophy in their relevance in the contemporary context. This research uses a qualitative approach to literature study or literature review. This approach involves collecting and analyzing information from various written sources such a books, scientific journals, and articles.